Las jurisdicciones de control abstracto de constitucionalidad en el modelo federativo Brasileño - Viveiros, Mauro [UNESP] (My University, 2013)
In this article the objective is commit about the subsystem of abstract control of constitutionality in the Brazilian constitutional legislation, theme not much studied that suggest interesting questions about it operation. Our objective is to emphasize, specially, appearance about the autonomy of this subsystem, in the way of the integration and the relation with the general system, concentrated in the Supremo Tribunal Federal, considering the model of the distribution of the legislative power in our federative model, and the need of preservation of the public's fields that belongs to the Union and to the members states down the principles of the unit and equality.
Keywords: Abstract control; Autonomy; Competency; Distribution; Federation; Integration; Jurisdiction; Relation; Subsystem; System